Effect of Pressure on Frequency Stability and Regulator Response in an LPG-Fueled Generator Set - Rizqi, Muhammad Ihsanul; Kusumawardana, Arya; Isrofiasrory , Rey Gasta (Universitas Muhammadiyah Yogyakarta, 2026)
The increasing demand for electrical energy has led to the extensive use of generator sets as backup power sources, particularly in areas with unstable grid supply. However, conventional generator sets operating on petroleum-based fuels are associated with low efficiency and high exhaust emissions. Liquefied Petroleum Gas (LPG) is considered a cleaner alternative, although its performance strongly depends on the stability of gas supply pressure. Previous studies have generally evaluated generator performance based on output characteristics without simultaneously examining the interaction between cylinder pressure, hose pressure, and the mechanical response of the regulator. This study addresses this gap by examining the combined effects of LPG cylinder and hose pressures on frequency stability and regulator behavior during generator operation. Experimental tests were conducted on an LPG-fueled generator set under load variations of 0%, 25%, 50%, and 75%. Cylinder pressure, hose pressure, regulator opening angle, and output frequency were measured simultaneously using pressure, position, and electrical measurement sensors. The results demonstrate a statistically significant correlation between gas pressure and frequency stability. Stable operation was achieved when hose pressure was maintained within the range of 0.8-1.0 psi, resulting in output frequencies of 49.8-50.2 Hz, whereas pressures below this range caused significant frequency deviation. These findings confirm that maintaining stable gas pressure is essential for achieving optimal frequency performance and provide practical insights for improving regulator design in LPG-fueled generator systems.